Modelos matemáticos e análise fractal na investigação da inativação fotodinâmica de microrganismos fitopatogênicos - Kalck, Alessandro da Silva (2017)
The increasing and indiscriminate use of pesticides may lead to intoxication in living organisms as well as contamination of environment and foods. In addition, pesticides can cause resistance, promoting the selection of resistant phytopathogenic microorganisms. This is a major problem in the agricultural and human health areas, which leads to the need to develop new methodologies to address this problem. Photodynamic inactivation (PDI) is a promising strategy involving the association of a photosensitizer (PS), light, and molecular oxygen to inhibit the growth of microorganisms. In this work, the PS orange acridine, OA, was deposited using the layer-by-layer spray technique, which was chosen because of its ease to application in ambient condition and high control of the deposition area. The effectiveness of the method was evaluated by the analysis of the growth evolution of the colonies as a function of the amount of PS layers applied in ambient condition at presence of the sunlight. It was used image processing and analysis of the fractal theory in evaluating the growth of the colonies. The results revealed that OA is a candidate to PS for using in ambient condition. It was possible to observe the reduction of the growth dynamics of the colonies with the increase of the number of PS layers. This suggested that the decrease could be caused by the photoinactivation. The parameters related to the fractality of the system were described by mathematical models of fractal growth of interfaces. The knowledge of these parameters can help to identify new strategies for the control of phytopathogenic microorganisms that directly affect agricultural production.